IMPLEMENTASI RELIGIUS KULTUR DALAM MEMBENTUK KARAKTER SISWA DI SMP ASSALAAM BANDUNG - Muhammad Taufiq Nur Rohman; Fiki Inderasyah; Mastuhi (STAI Pelabuhan Ratu, 2023)
The Islamic religious education system in schools is a form of elaboration of the mandate of Law Number 20 of 2003 concerning the National Education System, in order to prepare students to become human beings of faith and piety and morality, but in practice they have drawn criticism from the public that PAI in schools So far, it has been assessed that it only equips students with religious knowledge (cognitive) with less emphasis on practical aspects (affective and psychomotor). If it is necessary to develop PAI itself, so that PAI is not only limited knowledge but can also be practiced in everyday life both at school and in the everyday environment. Both by teachers, and students. Therefore, it is necessary to build a religious culture in religious activities in schools to enhance affective practice in harmony with educational goals. The purpose of writing this article is to implement a cultural-religious system in shaping the character of students at Assalaam Middle School Bandung. This approach uses qualitative, through the case study method. The results of this study state that the implementation of religious culture has been running for a long time and is also supported by a special curriculum, namely the greeting curriculum which is a means of religious culture in schools. Even though it has been implemented, there are still obstacles and problems experienced by the Principal, PKS Curriculum, Student Affairs, PAI teachers and students. As a form of overcoming problems and obstacles.